Faktor Risiko Katarak di Wilayah Kerja Puskesmas Astambul, Kabupaten Banjar, Kalimantan Selatan, Indonesia - Martyana, Dina Eka (PT Kalbe Farma Tbk., 2024)
Background. Indonesia has the highest prevalence of blindness in Southeast Asia; 81.2% are caused by cataracts. The prevalence of cataract blindness in South Kalimantan was 87.9%. Risk factors for cataracts include age, sex, comorbidities, such as diabetes mellitus and hypertension, steroid use, history of smoking, and exposure to ultraviolet radiation. This study aims to determine the risk factors and incidence of cataracts in the area of Astambul Community Health Center. Method. An observational analytical study with a cross-sectional approach. Primary data from January-February 2023 was collected from health center, posbindu and elderly posyandu visits. The data was analyzed with a chi square test. Results. p-value for age was p=0,046, gender p=0,251, occupation p=0,027, diabetes mellitus p=0,028, and hypertension p=0,023. Conclusion. A significant relationship between cataract incidence and age, diabetes mellitus, hypertension, and occupation. There is no significant relationship between cataract incidence and gender.